Osteosarcoma in Patients with Rothmund–Thomson Syndrome. (1st February 2015) - Zils, Katja; Klingebiel, Thomas; Behnisch, Wolfgang; Mueller, Hermann L.; Schlegel, Paul-Gerhardt; Fruehwald, Michael; Suttorp, Meinolf; Simon, Thorsten; Werner, Mathias; Bielack, Stefan
Abstract : Background : Rothmund–Thomson syndrome (RTS) is associated with an increased risk of osteosarcoma, but information about affected patients is limited. Procedure : Seven patients with osteosarcoma, treated in the Cooperative Osteosarcoma Study Group-trials, had a diagnosis of RTS. Their patient-, tumor- and treatment-related variables and outcome were reviewed retrospectively. Results : Median age at diagnosis of osteosarcoma was 13 years (range 7–16), five were female, two male. Tumor involved proximal tibia ( n = 4), distal tibia ( n = 1), distal fibula ( n = 1) and proximal ulna ( n = 1). Three patients had metastatic disease at diagnosis. All patients received surgery and chemotherapy. Four of seven patients required dose modifications and three of them terminated treatment prematurely. Complete resection of the primary tumor was achieved in all individuals. Two of three affected patients failed to achieve surgical clearance of their primary metastases and died. The third patient relapsed with multiple metastases and died. Two of four patients with localized disease were alive in first complete remission, a third patient in second complete remission after recurrence and a fourth patient died of acute leukemia, while still in first complete remission of osteosarcoma. Conclusions : Patients with RTS and osteosarcoma may be cured of their cancer with appropriate multimodal therapy. They should be treated like other osteosarcoma patients but preexisting disorders, needs for special support and development of toxicities have to be considered.